Aerostat-Based Observation of Space Objects in the Stratosphere - Jiang Wang; Ming Shen; Qin Wen; Rong Zhao; Zhanchao Wang; Pengqi Gao; Min Huang (Applied Sciences, 2024)
For the requirements of the multi-means observation and emergency monitoring of space objects, including space debris and near-earth asteroids, this paper analyzes the astronomical observation conditions in the stratosphere, which is the region of the earth’s atmosphere between 18 km and 55 km of altitude. The results reveal that near space has a significantly superior sky background and observation environment than ground-based observation, with the values of transmittance in the visible band and near-infrared bands more than 0.91 and 0.988, respectively. The sky background radiance at 20 km is 2.5% of the ground in the visible band and near-infrared band, which is practical for daytime observation, and there is an advantage in the availability of observable hours without the influence of aerosols and turbulence, etc. Based on near-space aerostats, such as a high-altitude balloon, a new method of space object floating observation has been proposed, including the observation facilities and scheme. The simulation shows that it has an all-weather/all-day ability while adopting multi-band observation. Applying a telescope with 9.5 mag detective ability located on the aerostat, debris with the size of about 0.36 m can be observed at a 1000 km distance and phase angle of 100°, while the near-earth asteroid with the size of about 980 km can be observed at a 5 million km distance and phase angle of 40° during the daytime. With these advantages, the aerostat-based observation would be a beneficial supplement to the ground-based observation network.